The experience of black parents/caretakers with the births and care of a child with profound congenital defects - M.S. Mabaso; L.R. Uys (AOSIS, 1990)
The reaction of Black families to the birth and care of a baby with profound congenital defects was researched using twenty case studies. It was found that the families went through stages of the grieving process, that they shifted from the Western/Christian viewpoint to the traditional viewpoint in their struggle to cope and that they find the existing services grossly inadequate.